Comparative Study of Fuzzy Query Vector Modification and Fuzzy Radial Basis Function method for Images Retrieval - Tatik Maftukhah (INKOM Journal, 2011)
This paper describes the use of Fuzzy Query Vector Modification (QVM) and Fuzzy Radial Basis Function (RBF) method for image retrieval. Both methods used relevant feedback process to obtain images according to the wishes of the user. The proposed research is Fuzzy QVM method uses six levels, consisting of: very relevant, relevant, few relevant, vague, non relevant, and very non relevant. Fuzzy RBF method uses three levels, consists of relevant, fuzzy, and non relevant. Testing is done by calculating the precision value at several recall levels. The result test is known as Fuzzy QVM method provides higher precision than Fuzzy RBF with comparative value is 1 : 0.8255.  The research concluded the Fuzzy QVM method better performance than Fuzzy RBF method.